Creating Successful Collaborations between Startups and Large Corporations within the AEC sector A qualitative study of the motives, challenges and critical factors in collaboration - ALKALALI, DOAA; MALMQVIST, ERIK (My University, 2020)
Actors within the AEC sector have traditionally been notorious for conservative mindsets and failure to utilize innovation. Members of other sectors have accomplished more in this regard and increased their trust in external parties to be part of the innovative advancement, for example through startups. Thus, the aim of this report is to establish understandings of the synergies between startups and large corporations within the construction industry, with the primary perspective being that of the large corporations. The main research question investigated was “How can large-sized construction companies and startups create successful collaborations?”. In order to attain this aim, the study was conducted by combining a literature review with an empirical study, based in the Swedish construction industry. The study has found that startups and large corporations within the AEC sector have complementary attributes. From the startup perspective, the motives behind collaboration include (1) the possibility to validate ideas with help of feedback; (2) attaining experience and knowledge of the sector; (3) receiving help in defining problems to solve; (4) receiving economic funding when co-developing products; (5) the possibility to scale ideas once being validated; (6) gaining credibility. On the other hand, desires of the large corporations include (1) being introduced to new solutions; (2) challenging established ways of operating; (3) accessing agile processes when co-developing products; (4) reducing the costs related to innovation; (5) obtaining custom-made products; (6) enhancing market image. Advantageously, the collaborative approaches are to be formalized and a reasonable point of departure for large-sized firms is to make sense of their contemporary situation and acknowledge how the motives apply to their respective core strategies. In addition, critical factors need to be managed by the large corporation in order for the partnerships to be categorized as successful. In this sense, it is of importance that (1) an obvious entry point for startups is created at the large corporation; (2) the collaboration objectives and procedures are clarified; (3) the large corporation establishes a higher sense of urgency; (4) sufficient resources and involvement of appropriate participants are provided.
Keywords: large corporation; startup; AEC sector; innovation; startup-corporation collaboration; collaboration motives; collaborative approaches